PENINGKATAN MOTOVASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN MAKE A â€“MATCH DENGAN MEDIA â€œBESIâ€ PADA MATA PEMBELAJARAN PKN DI KELAS VIII.2 SMPN 3 KOTO BARU - anwar, yenita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2020)
The aim of this action research is to improve studentsâ€™ motivation learning for PKn sabject by using â€œIronâ€ media throught Make A Match model at SMPN 3 Koto Baru Dharmasraya. Action research ha done two sycles. Each sycles for two time meeting using Make A Match model.For collecting data used observation sheet in sycle 1and 2. Resulting action research of motivationlearning about teacher activities are increasing. The first sycle get 90 % is in good category and the second sycle get 97% is in good category too. For the students activities are able to reach 71,21 % in sycle 1 that is a good category and sycle 2 students activities are able to reach 87,12% that is very good category. Resulting of studens motivation can be shown to indicator of â€˜diligent for doing taskâ€™ in sycle 1 are able to reach 76% and sycle 2 is 94%. Indicator ofâ€™strong of confront troubleâ€™in sycle 1 is 53%, in sycle 2 to be 67%. Indicator of â€˜showing interest for varieting problem in sycle 1 is 42% and sycle 2 is increasing to be 60%. For indicator â€˜more like to selftaughtâ€™its getting 2,3% for sycle 1 and sycle 2 just to reach 2,2%. Indikator â€˜boring to routine tasksâ€™ is getting 22% to be 3,6%. Indicator â€˜maintaining opinionâ€™is 4,5% is increasing to be 23%. Indikator â€˜has the establishment of is 16% in sycle 1 and sycle 2 is in 16% too. For indicator â€˜like finding and solve the problem,it is lower from 12% to be 11%. Resulting of research is able to be summary that a Make A Match model by using â€œironâ€ media is able to improve studentâ€™s motivation in learning of PKn sabject to students of VIII.2 class of SMPN 3 Koto Baru Dharmasraya at 2017/2018 sabject years.